Impact of seawater intrusion and disposal of desalinization brines on groundwater quality in El Gouna, Egypt, Red Sea Area. Process analyses by means of chemical and isotopic signatures. (January 2019) - Jahnke, C.; Wannous, M.; Troeger, U.; Falk, M.; Struck, U.
Abstract: The processes of seawater intrusion, groundwater abstraction and disposal of high concentrated effluents from desalinization plants (DSP) were investigated in a coastal aquifer on the Red Sea coast of El Gouna, Egypt. The feeding wells (depths from 20 to 150 m), the product water and the residual brines of three desalinization plants were sampled for chemical analysis and were partially sampled for stable isotopes analysis (δ 18 O and δ 2 H in H2 O). The wells in the aquifer abstract mixtures of brackish groundwater (total dissolved solids TDS 5–15 g/l) and seawater from the Red Sea (TDS 42–44 g/l) that intrudes into the coastal aquifers. Primary mixing rates were determined by means of the Br/Cl ratio and ranged from 5% to >90% seawater. The disposal of the highly concentrated residual brines from the DSPs via infiltration/injection into the used aquifer causes a locally strong increase in the salinization of the groundwater (up to 60 g/l TDS, significantly above seawater concentration) in wells that are actually feeding the DSPs (containing up to 60% brine). The influence of the brines on the groundwater could also be identified by the Br/Cl ratio in relation to salinization. Conversely, the primary source (the mixing ratio groundwater-seawater) of the brines from the DSP could also be identified by Br/Cl ratio and stable isotopes (δ 18 O and δ 2 H in H2 O), which behave as conservative tracers in the reverse osmosis processes in the DSP. The brackish groundwater shows partially gypsum saturation and supersaturation. Mixing of this groundwater with seawater additionally increases the sulphate concentration and cation exchange processes and especially the calcium concentration. The abstracted groundwater and groundwater-seawater mixtures therefore have a high potential for sulphate scaling. Calcite, as the second important phase for scaling, is generally supersaturated in groundwater, seawater and the mixtures. Consequently, the brines that are produced from these waters are highly supersaturated with respect to gypsum and calcite. The injection/infiltration of these brines into the aquifers leads to extended zones of groundwater with increased salinity and saturation/supersaturation in respect to gypsum and probably intense gypsum precipitation. Highlights: Influences of brine disposal from desalinization plants and seawater intrusion on groundwater quality in a coastal aquifer are quantified. Br/Cl ratio, δ 18 O and δ 2 H in H2 O are used as proxies for the primary sources of salinity. Br/Cl ratio, δ 18 O and δ 2 H in H2 O behave as conservative tracers in the reverse osmosis processes of desalinization.brine disposal leads to zones with increased salinity and saturation/supersaturation with respect to gypsum in the aquifer Brine disposal leads to zones with increased salinity and saturation/supersaturation with respect to gypsum in the aquifer.